Design & vidro : a herança da industria nacional da Marinha Grande - Gato, Aurora Faustino, 1992- (2018)
Glass is described as a fragile and transparent material, whose presence manifests itself in the most diverse and almost unnoticed forms in human daily life: Whether it’s the window that connects us to the outside, the glass of wine on the table or the magnificent stained-glass windows in cathedrals. If we think further on about this material, we come to the conclusion that it’s history is undoubtedly tangled up with ours, keeping us from even realizing the exact moment when the first contact between both was made. Or when the human being started to manipulate glass. It is the ambiguity of glass that makes it such an interesting and sought-after material. Since its discovery, the crafting mastery has evolved and matured to the most elaborate forms, from glass cane to the automatics, glass is constantly evolving. And as history shows until today, glass has a special place both in our architecture and at our tables. Glass has become common, but has never lost its magical glint, for which it was always desired over time. It has a special place in our daily lives and in art. A symbolic reading on glass, points to it’s importance, highlighting it’s presence in Art and Design, both for it’s aesthetic peculiarities and for its pragmatic utilities that seduce our minds. It's with this goal in mind that our investigation features the material and the artists that manipulate it. It's about an ancestral bond requiring rigorous labor in which the artist plays a special part,both nationally and abroad, which leads us to refer to Marinha Grande, the "capital of glass" in Portugal. It is in the national context that we focus the main effort of getting to understand this material in our history, industry and art. The results of the connection between industry and art show us how fascinating glass is, from the old times to contemporary times - we can call it a timeless fascination